The spectrum of neoplasms of uterine cervix and their clinico-morphological correlation in tertiary care center in dakshina Karnataka - Dr. Tanvi Shetty; Dr. Nikitha Kairanna; Dr. Brij Mohan Kumar Singh; Dr. Pavithra P.; Dr. Varun Kumar Singh (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: Cervical carcinoma is one of the leading causes of death among women worldwide. An estimated of 2,30,000 women die annually from cervical cancer, and almost 1,90,000 are from developing countries. It is considered to be the 3rd most common malignancy among women.Materials and Methods: This is a 5 year retrospective study done in the department of pathology, Kasturba medical college, Manipal. Hysterectomy and cervical biopsies are included in this study. Clinical details were obtained from case sheets.Results: 175 cases of cervical neoplasms were studied in total. The patient’s age was ranged 21 to 80 years with mean being 50.5 years. Among the commonest complaints was post-menopausal bleeding followed by menorrhagia and intermenstrual spotting. 49% cases had a growth in the cervix followed by 12% cases with induration and 10% cases as polyp in cervix. Among the 175 cases, 14.86% cases were precursor lesions. Among the malignant cases, squamous cell carcinomas (61.71%) were the commonest. Rare tumour includes 2.86% cases of minimally invasive carcinoma, 1.71% cases of neuroendocrine carcinoma, and 1.14% cases each of serous carcinoma.Conclusion: Neoplastic lesions from the uterine cervix comprise of a wide variety of lesions originating from both the epithelial and stromal elements. Among the malignant tumours, squamous cell carcinoma was very common. Hence, a thorough clinical evaluation and post-menopausal health check-ups along with detailed cervical examination and microscopic evaluation is the key towards correct and timely diagnosis of cervical neoplasms.